Band modification of graphene by using slow Cs+ ions. Issue 11 (22nd January 2016) - Sung, Sijin; Lee, Sang-Hoon; Lee, Paengro; Kim, Jingul; Park, Heemin; Ryu, Mintae; Kim, Namdong; Hwang, Choongyu; Jhi, Seung-Hoon; Chung, Jinwook
Abstract : We report new wide band gap engineering for graphene using slow Cs + ions, which allows both fine-tuning and on–off switching capability of the band gap in a range suitable for most applications sustaining the nature of Dirac fermions. Abstract : We report new wide band gap engineering for graphene using slow Cs + ions, which allows both fine-tuning and on–off switching capability of the band gap in a range suitable for most applications without modifying or deteriorating the relativistic nature of the Dirac fermions. The doping of Cs + ions opens the band gap up to E g = 0.68 eV, which can be closed completely by adding neutral Cs atoms, as observed in angle-resolved photoemission spectroscopy. The operating mechanism of this band gap engineering is understood by a simple capacitor model, which is fully supported by the density-functional theory calculations.